Efficient in vivo and in vitro assembly of retroviral capsids from Gag precursor proteins expressed in bacteria - Klikova, M; Rhee, S S; Hunter, E; Ruml, T (Journal of virology, 1995)
The capsid precursor protein (Gag) of Mason-Pfizer monkey virus, the prototype type D retrovirus, has been expressed to high levels in bacteria under the control of the phage T7 promoter. Electron microscopic studies of induced cells revealed the assembly of capsid-like structures within inclusion bodies that formed at the poles of the cells 6 h after induction with isopropyl-beta-D-thiogalactopyranoside (IPTG). The inclusion bodies and enclosed capsid-like structures were solubilized completely in 8 M urea, but following renaturation, we observed assembly in vitro of capsid-like structures that demonstrated apparent icosahedral symmetry. These results demonstrate for the first time that retroviral capsid precursors have the propensity to self-assemble in vitro and point to new approaches for the analysis of retroviral assembly and structure.
Keywords: HeLa buňky; Gene Products, gag; Masonův-Pfizerův opičí virus; buněčné inkluze virové; Mason-Pfizer monkey virus; genové produkty gag; Protein Precursors; Inclusion Bodies, Viral; lidé; Escherichia coli; proteinové prekurzory; kapsida; HeLa Cells; Humans; Capsid